The achievement of Hans Urs von Balthasar: an introduction to his trilogy - Levering, Matthew (Catholic University of America Press, 2019)
Intro -- Contents -- Foreword by Cyril O'Regan -- Acknowledgments -- Introduction -- 1. Theological Aesthetics: A Kantian Critique of Kant -- 2. Theo-Drama: A Hegelian Critique of Hegel -- 3. Theo-Logic: A Nietzschean Critique of Nietzsche -- Epilogue -- Bibliography -- Index.